Quantitative fetal fibronectin predicts preterm birth in women with bulging fetal membranes. (August 2016) - Fiorini, Francesco; Isted, Alexander; Hezelgrave, Natasha L.; Shennan, Andrew H.
Abstract: Objective: To assess the predictive value of quantitative fetal fibronectin (fFN) concentration in cervicovaginal fluid for spontaneous preterm birth in women with bulging fetal membranes. Study design: This was a prospective observational study from five UK tertiary centres of a cohort of women with singleton pregnancy and bulging fetal membranes presenting between 18 and 32 weeks of gestation ( n  = 62), in the period 2010–2014. fFN concentrations in cervicovaginal fluid were measured both quantitatively and qualitatively at presentation in all women. Predictive statistics and receiver operating characteristic (ROC) curves were calculated for both tests to predict spontaneous preterm birth within 14 days from testing and before 34 weeks of gestation. Results: 62 eligible women with bulging fetal membranes were recruited from screening of 2571 women at high risk of preterm birth. The median gestational age was 24 +0 (LQ-UQ, 21 +2 –25 +3 ) at presentation and 34 +4 (25 +2 –39 +0 ) at delivery, with a median time from testing to delivery of 58 days (17–110). Concentration of quantitative fFN at presentation correlated negatively with time to delivery (Spearman's r s  = −0.615, p  < 0.001). The area under the ROC curve for quantitative fFN testing was 0.81 (95% CI 0.69–0.94) for prediction of spontaneous preterm birth within 14 days, and 0.84 (0.73–0.95) before 34 weeks of gestation. Conclusion: Quantitative fFN has a role in predicting spontaneous preterm birth even in women with bulging fetal membranes, suggesting that fFN leakage could potentially be an active process. This may aid the clinical management of this high-risk group in the future.